Analisis Kesalahan Penggunaan I-keiyoushi Dan Na-keiyoushiDalam Menulis Sakubun pada Mahasiswa Program Studi Pendidikan Bahasa Jepang Tingkat II Universitas Riau - Lestari Astiwi Astiwi; Sri Wahyu Widiati Wahyu Widiati; Nana Rahayu Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research discusses about the results of the error analysis using i-keiyoushi and na-keiyoushi on student essays. The purpose of this study was to determine the types of errors that appear in any use of i-keiyoushi and na-keiyoushi and percentage of errors in the use of adjectives i-keiyoushi and na-keiyoushi.This research is a qualitative research with descriptive method. This research was conducted in Japanese Language Education department Teacher is Training andEducation Faculty of the Riau University. The research data was obtained from three theme of essay with the total of 80 essays.The basic theory used in this study is the surface strategy taxonomy proposed by Heidi Dulay et al.This stages of this reseach consisted of identifiying errors, caculating the precentage of errors, and analizing the errors of the sentences.The results of this study shows that the type of errors which occurred the most is misformation error with the total of 29 out of 70 errors, while the least error is misordering error with the total of 5 out of errors. The total of the other types are 13 errors for omission, 12 errors for addition, and11 errors for alternating form. It shows that the students have goodunderstanding in using i-keiyoushi and nakeiyoushi in their writings. Keywords: Error Analysis, sakubun, writing, i-keiyoushi, na-keiyoushi